Fåglar i urbana miljöer : kvaliteten på urbana habitat och om beståndstäthet är ett bra mått på habitatkvalitet - Jansson, Mattis (SLU/Dept. of Ecology, 2010)
The urbanization of the world is increasing. How it affects bird populations have been well studied during the last decade, and comparisons between urban and non-urban habitats have been carried out. A common method for measuring habitat quality is to calculate the population density. This method is easy to use, but have been criticized during the last couple of years. In this study, data of population densities was compared with data on reproduction success. The results show that the population density for birds in general is higher in urban habitats compared to non-urban habitats. However, data shows that the reproduction success is lower in urban habitats, indicating that the quality of urban habitats nevertheless is low. This also suggests that calculating population densities is not a good method for measuring habitat quality. Factors that affect reproduction success should be used instead. From the view of conservation biology, this result is important. It is of major interest that resources are given to the right habitat. However, more studies need to be done. For instance the mortality of adult birds need to be studied in a more proper way, which will give more exclusive answers about the life histories of bird individuals.